Quantification of Pelvic Mobility on Dynamic Magnetic Resonance Images: Using Mechanical Insight to Help Diagnose Pelvic Pathologies. (8th July 2015) - Lecomte‐Grosbras, P.; Witz, J.‐F.; Brieu, M.; Faye, N.; Cosson, M.; Rubod, C.
Abstract Pelvic mobility is essential for good pelvic organ function. Any modification may be a sign of pathology. The objective of this study was to define a methodology to quantify pelvic mobility. An analysis protocol based on an image registration technique performed on dynamic magnetic resonance imaging sequences is presented. A methodology is proposed for measuring and analysing the whole displacement field based on the contour of the four pelvic organs: the vagina, bladder, rectum and uterus. A targeted analysis of pelvic mobility can be applied in the normal, hypermobility and hypomobility context. The quantification of pelvic mobility in normal conditions allows localising fascia or ligaments involved in the static of pelvic organs. In pathological situations such as prolapse, it helps localise a suspension structure weakness. In a context of hypomobility such as deep pelvic endometriosis, it should help localise pathologic areas to provide more relevant diagnosis and treatment. When combined with conventional radiology, this analysis protocol can be applied to the diagnosis and assessment of complex pelvic pathologies to help define the most suitable surgery. Moreover, these experimental results obtained in normal and pathological cases will help build and validate a better mechanical finite element model of the pelvic system.